British University System: Historical and Pedagogic Aspects - O. O. Chertovskikh (Vestnik MGIMO-Universiteta)
The article offers a historical survey of the British university system as part of the history of education. The author stresses the importance of the cultural aspect in preparing Russian university students and staff members for internship, language training and further education in British universities within the system of European academic mobility.